Unraveling the ubiquitin‐regulated signaling networks by mass spectrometry‐based proteomics. Issue 3 (26th November 2012) - Low, Teck Yew; Magliozzi, Roberto; Guardavaccaro, Daniele; Heck, Albert J. R.; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> Ubiquitin (Ub) is a small protein modifier that is covalently attached to the ε‐amino group of lysine residues of protein substrates, generally targeting them for degradation. Due to the emergence of specific anti‐diglycine (‐GG) antibodies and the improvement in MS, it is now possible to identify more than 10 000 ubiquitylated sites in a single proteomics study. Besides cataloging ubiquitylated sites, it is equally important to unravel the biological relationship between ubiquitylated substrates and the ubiquitin conjugation machinery. Relevant to this, we discuss the role of affinity purification‐MS (AP‐MS), in characterizing E3 ligase‐substrate complexes. Recently, such strategies have also been adapted to screen for binding partners of both deubiquitylating enzymes (DUBs) and ubiquitin‐binding domains (UBDs). The complexity of the "ubiquitome" is further expanded by the fact that Ub itself can be ubiquitylated at any of its seven lysine residues forming polyubiquitin (polyUb), thus diversifying its lengths and topologies to suit a variety of molecular recognition processes. Therefore, applying MS to study polyUb linkages is also becoming an emerging and important area. Finally, we discuss the future of MS‐based proteomics in answering important questions with respect to ubiquitylation.